SHARIA BUSINESS LEGAL PROTECTION FOR CUSTOMERS WHO ARE VICTIMS OF FRAUD AT INDONESIAN SHARIA BANKS - Ramadhan, Munawwir; Fadhil, Muhmmad (Program Pascasarjana UIN Sumatera Utara Medan, 2026)
The increasing incidence of fraud in the Islamic banking sector, particularly at Bank Syariah Indonesia (BSI), indicates a gap in the supervision system and legal protection for customers. This study aims to analyze the forms of legal protection under Islamic business law for BSI customers who have become victims of fraud between 2023 until 2025, as well as to assess the effectiveness of the application of Sharia principles and positive law regulations in safeguarding customers’ rights. The research employs a juridical-normative method by using a statute approach and a case approach, with secondary data derived from court decisions, Financial Services Authority (OJK) reports, and official national media publications. The results show that the legal protection mechanisms for BSI fraud victims have not been fully optimal. Although dispute resolution mechanisms exist through the Financial Services Authority (OJK) and the Alternative Dispute Resolution Institution for the Financial Services Sector (LAPS SJK), their implementation still faces challenges regarding transparency and case-handling efficiency. From the perspective of Islamic law, the principles of amanah (trustworthiness), ‘adālah (justice), and maslahah (public interest) have not been fully applied in protecting customers, particularly in cases of internal and cyber fraud. This study recommends strengthening the responsibilities of Islamic banks, including ensuring data confidentiality, regulatory compliance, employee training, and the implementation of comprehensive digital security systems. Technological innovations such as data encryption and blockchain utilization are essential strategies for protecting customers’ data from potential misuse. Furthermore, banks are obliged to provide compensation to affected customers as a form of legal accountability, either through non-litigation mechanisms (LAPS) or litigation in Religious Courts, in accordance with the characteristics of Islamic Business Law. Therefore, the protection of Islamic business law for customers should not only be reactive after fraud occurs but also preventive, aiming to maintain public trust and ensure the sustainability of Islamic banking in Indonesia.